A sustainable vanadium bioremediation strategy from aqueous media by two potential green microalgae. (15th April 2023) - Tambat, Vaibhav Sunil; Patel, Anil Kumar; Chen, Chiu-Wen; Raj, Tirath; Chang, Jo-Shu; Singhania, Reeta Rani; Dong, Cheng-Di
Abstract: Globally, environmental concerns are rapidly growing due to increasing pollution levels. Vanadium is a hazardous heavy metal that poses health issues with an exposure concentration of about 2 ppm. It is regularly discharged by some industries and poses an environmental challenge. There are no sustainable green treatment methods for discharged effluents to mitigate vanadium threats to humans and the environment. In this study, the goal was to develop a green, sustainable method for removing vanadium and to utilize the produced biomass for biofuels, thus offsetting the treatment cost. Microalgae Chlorella sorokiniana SU1 and Picochlorum oklahomensis were employed for vanadium (III) treatment. The maximum removal was 25.5 mg L −1 with biomass and lipid yields of 3.0 g L −1 and 884.4 mg L −1 respectively after 14 days of treatment. The vanadium removal capacity by microalgae was further enhanced up to 2–2.7 folds while optimizing the key parameters, pH, and temperature before removing biomass from the liquid phase. FTIR is used to analyse the reactive groups in algal cell walls to confirm vanadium adsorption and to understand the dominant and quantitative interactions. Zeta potential analysis helps to find out the most suitable pH range to facilitate the ionic bonding of biomass and thus maximum vanadium adsorption. This study addresses regulating external factors for enhancing the removal performance during microalgal biomass harvesting, which significantly enhances the removal of vanadium (III) from the aqueous phase. This strategy aims to improve the removal efficiency of microalgal treatment at an industrial scale for the bioremediation of vanadium and other inorganic pollutants. Graphical abstract: Image 1 Highlights: Algae are emerging as an effective bioremediation platform for vanadium pollution. The maximum vanadium adsorption determined 7.53 mg g −1 dry algae biomass. Maximum removal efficiency obtained 51% with 50 mg L −1 initial V(III) concentration. During harvesting, pH 3 and 35 °C offered maximum V(III) removal of 25.5 mg L −1 The maximum microalgae biomass and lipid yields were 3.0 g L −1 and 884.4. mg L −1 .